2017
DOI: 10.18869/nirp.jmr.11.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intramuscular Electrical Stimulation on Symptoms Following Trigger Points; A Controlled Pilot Study

Abstract: Introduction: Myofascial Pain Syndrome (MPS) is a common disorder of musculoskeletal system. About one third of the people with musculoskeletal disorders have been diagnosed as having MPS. It is a painful condition caused by trigger points. A variety of treatment approaches are used to cure MPS and its associated disorders. This study aimed to investigate the effects of single session Intramuscular Electrical Stimulation (IMES) through dry needling on pain and Range Of Motion (ROM) following trigger points in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…All articles that analyzed the effect of PNM on pain found significant improvements. The studies made by Hadizadeh et al [ 23 ] in patients with trigger points in upper trapezius, Botelho et al [ 16 ] in patients with myofascial pain syndrome, da Graca-Tarragó et al 2016 [ 17 ] in patients with knee osteoarthritis, and Raphael et al [ 33 ] in patients with chronic pain and hyperalgesia obtained a significant improvement when it came to pain intensity ( P ≤ .048; P < .001; P = .001, and P < .0005, respectively). Likewise, García-Bermejo et al 2020 found a significant improvement on PNM based treatment when treating unilateral anterior knee pain, regardless using it in a contralateral or homolateral manner ( P = .01 in both groups).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All articles that analyzed the effect of PNM on pain found significant improvements. The studies made by Hadizadeh et al [ 23 ] in patients with trigger points in upper trapezius, Botelho et al [ 16 ] in patients with myofascial pain syndrome, da Graca-Tarragó et al 2016 [ 17 ] in patients with knee osteoarthritis, and Raphael et al [ 33 ] in patients with chronic pain and hyperalgesia obtained a significant improvement when it came to pain intensity ( P ≤ .048; P < .001; P = .001, and P < .0005, respectively). Likewise, García-Bermejo et al 2020 found a significant improvement on PNM based treatment when treating unilateral anterior knee pain, regardless using it in a contralateral or homolateral manner ( P = .01 in both groups).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant improvement in three out of six articles that analyzed this parameter. In patients with trigger points in upper trapezius ( P = .048), [ 23 ] patients with bilateral reduced hamstring syndrome ( P < .01), [ 21 ] and patients with anterior knee pain ( P = .001). [ 22 ] Nonetheless, de la Cruz et al 2019 found no significant improvement in ballet dancers, [ 19 , 21 ] nor did Sumen et al in patients with trigger points in upper trapezius.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular electrical stimulation (IMES) is an electrotherapeutic modality that uses needles to deliver electrical current into muscles and, more specifically, into TrPs [ 42 ]. The electrical stimulation is often used as an additive to manual needling.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both electrical and manual stimulation of needles have overlapping physiological mechanisms due to the insertion of needles [ 43 ]. Evidence is gradually accumulating to support the use of IMES in patients with MPS [ 39 , 42 , 44 , 45 , 46 ]. However, a recent systemic review on IMES reported that among the six included studies, only three directly targeted TrPs [ 47 ].…”
Section: Introductionmentioning
confidence: 99%